RUSSIAN LANGUAGE CLASSES USING INFORMATION TECHNOLOGIES (Web of Teachers: Inderscience Research, 2024)
This article talks about the role and importance of using the media in learning the Russian language, the relevance of this application, which helps improve students’ media literacy. Explain the understanding of media literacy, media environment, media text.